Prototype Of Automatic Clothes Folding Device Based On Arduino Uno (Liquid Crystal Display) For Clothes Convection - ahmad zaenul muttaqin; Abdi Pandu Kusuma; Yusniarsi Primasari (JOSAR (Journal of Students Academic Research), 2024)
Folding clothes is an important job in a convection, where when folding clothes must be neat so that when packing, consumers become interested. But many think that folding clothes is boring. From this problem, the researcher produced an automatic clothes folding device based on Arduino uno. It is hoped that it can make it easier and shorten the time in folding clothes in the middle to lower convection. The purpose of design and research is to be able to design and make a folding device with automatic drive, the size of the shirt that can be folded with an automatic mechanism folding device, namely Small (S), Medium (M), Large (L). This tool uses three servos for the drive, LCD and buzzer as a reporter of the display and sound. By testing the feasibility of the hardware and the entire prototype of the automatic folding tool used at the Ririn Tailor Convection in Blitar Regency, based on two sources, the first from the user test, the results of the user test that has been carried out 3 times per person obtained a value of 72,6% of the average percentage of each user test because it has not been exposed to water, then the second source of robotics system experts with 3 tests got a score of 75% because, the existence of construction less solid so less for the long term.